Reliability of Fear Assessment in Growing Pigs Exposed to a Novel Object Test in Commercial Conditions. Issue 3 (3rd July 2017) - Dalmau, Antoni; Mainau, Eva; Velarde, Antonio
ABSTRACT: The objective of this study was to assess the reliability and feasibility of a novel object test assessing fear in pigs in commercial conditions. A total of 18 commercial farms were visited, and 321 pens housing 4, 220 growing pigs were assessed. Three balloons were used as a novel stimulus. Measures were (a) the time it took for the first pig to contact 1 of the balloons, (b) percentage of nonhuman animals watching the balloons each for 10 s, and (c) percentage of animals touching the balloons during periods of 5 s. The time of the first pig to contact 1 of the balloons ranged from 0 s to 362 s. An effect of the farm was found ( p < .0001) for contact latency, ranging from 6.8 s to 73.3 s, but little difference was found in terms of intrafarm variability. Interobserver repeatability was also high in this measure, ranging from r = .74 to r = .96. As a result, it is concluded that contact latency could be a good measure to assess fear of a novel stimulus in commercial farms.